The Ambivalent Representation of the Orient in T. E. Lawrence’s Seven Pillars of Wisdom: A Triumph (1935) - Sonia Lamrani (Cahiers Victoriens et Edouardiens)
The literary output that was produced during the rise of the British Empire often reflected the imperialist spirit that dominated the world at that time. Travel writing was one of the major fields which prospered in parallel with the spread of British global paramountcy. This literary genre contributed to strengthening and legitimising the imperialist and colonialist expansion and therefore represents one of the prominent samples for the postcolonial analytical framework. This paper will focus on one of these travel accounts, Seven Pillars of Wisdom: A Triumph (1935), written by Thomas Edward Lawrence also known as ‘Lawrence of Arabia’. Drawing upon postcolonial literary criticism, this paper will show the way Lawrence simultaneously reaffirms and rejects the imperialist and colonialist discourse in his portrayals. This paper will shed light on the ambivalence which prevails in Lawrence’s representations of the Orient. On the one hand, this research shows the way Lawrence showcases examples of imperialist thinking by reproducing stereotypical representations of the Orient through excessive aestheticisation or demeaning of Oriental people and landscapes. On the other hand, this paper highlights Lawrence’s departure from the conventional imperialist discourse with more nuanced portrayals. This paper contends that Lawrence’s Orientalist discourse is much more ambivalent and subtle than the conclusions elaborated by Edward Said in his critical theory of Orientalism.